DEVELOPMENT AND PROBLEMS OF TENNIS IN THE REGION (Journal of Universal Science Research, 2023)
This article examines the development of tennis in Uzbekistan during the years of independence, including the development of tennis in the Kashkadarya region, the construction of modern tennis courts, the material and technical base and the formation of qualified coaches.